Potency of bioinsecticides against the cowpea bruchid, callosobruchus maculatus (F.) (Coleoptera:chysomelidae) in storage - Amritha Kumari S (Department of Agricultural Entomology, College of Horticulture, 2011)
The present study entitled ‘Potency of bioinsecticides against cowpea bruchid, Callosobruchus maculatus (F.) (Coleoptera: Chrysomelidae) in storage’ was undertaken to understand the feasibility of utilizing few biologically based grain protectants in post harvest storage of cowpea by investigating their biological efficacy and persistent/ residual toxicity.